Dynamics of parameters of ultrasonic, microbiological and cytological investigations in the treatment of postoperative wound complications using magnesium containing minerals in the elderly patients - Muntyan S.O.; Nosov A.Y.; Getman V.V.; Balash K.P.; Chernyak S.P.; Kruglyak N.L. (Medičnì Perspektivi)
57 patients aged over 60 years with various types of wound complications after surgery for abdominal and anterior abdominal wall were treated. Treatment of wound complications included both traditional methods and the use of packs of bishofit. Оn the third day after the start of treatment there was a significant decrease in almost all computing performance indices as compared with treatment using bishofit. On the day 7 a noticeable difference of wound cavity width by 62.88%, the volume of the wound cavity by 85.76% in patients of the second group as compared with patients of the first was noted. So, bishofit use in the form of compresses in the treatment of postoperative wound complications such as hematoma, seroma and infiltration leads to a significant reduction in wound exudation, rapid decline in the concentration of microorganisms in the wound; this reduces time of wounds healing and patients’ recovery.